The Implementation of Education Unit Curriculum in Special Condition in Physics Lessons at SMAN 18 Surabaya (Universitas Negeri Surabaya, 2022)
The COVID-19 pandemic has caused many changes in all aspects of life, including education, which continues to be implemented through a limited online learning system. This limitation underlies the emergence of relevant alternative curricula to simplify the revised 2013 curriculum. This study aims to analyze the implementation of the Education Unit Curriculum in Special Conditions in high school physics subjects and students' responses to the simplification. The method used is a mixed-method using the Explanatory Factor Analysis (EFA) technique with the Kaiser-Meyer-Olkin (KMO) test to determine the instrument's validity and the Cronbach Alpha test to determine the reliability of the instrument. Qualitative descriptive analysis was also carried out from interviews with students, teachers, and students. The factor analysis results using the Kaiser-Meyer-Olkin (KMO) test and the Cronbach Alpha test showed that the instrument was valid and reliable so that it could be used in research. The questionnaire and interview analysis results showed that the curriculum of the education unit under special conditions had been implemented well. This can be seen from the number of students during hybrid learning and the reduction in learning time. However, according to respondents, the essential competencies used are not simplified to maintain the quality of student competencies. Based on the analysis results, it can be concluded that the Implementation of the Education Unit Curriculum in Special Conditions has been carried out well. Students, teachers, and students support the implementation of the Education Unit Curriculum in Special Conditions during online learning or hybrid learning while still using the essential competencies in the Revised 2013 Curriculum. Keywords: Education unit curriculum in particular conditions, revised 2013 curriculum, high school physics learning